Methane production, emission and control during MSW landfilling. - Barry, D. L.; Smith, Richard; Gregory, R. G.; Harries, C. (Eurowaste, 2003)
Until quite recently the major emphasis on landfill gas control has related to ‘postcompletion’ of landfill cells or phases, rather than during active waste disposal operations. Increasingly, odour control needs have changed that pattern through ad hoc capping and gas collection systems but, to date, there has been little quantitative information available on the scale of methane emissions from the commencement of waste deposition. This applied research project involved extensive surface flux emission monitoring carried out on 21 operational UK landfills. Main findings were that (a) the onset of methanogenesis appears to occur within about 2 months of waste placement and is well-established, with methane at least 40% by volume, after about 6 months; and (b) surface methane flux emissions were detectable within about 1 month after waste placement. Additionally, surface flux data showed that (c) the emission rates from waste side slopes were much greater than from top surfaces, and (d) areas close to landfill edges can have the highest emission rates. Both of the latter findings confirm the high lateral (as opposed to vertical) permeability of landfilled wastes. Moreover, emission rates from top surfaces of waste do not appear to increase significantly with age. The average surface flux rate appeared to peak around 20-24 months (following initial waste placement) at about 1mg. m -2 .s -1 , but this result could be influenced by the particular conditions at the relevant sites. Nonetheless, the flux rate is some 100-times greater than the proposed UK limit for emissions from temporarily capped sites. The main zones where effective reductions can be made in emissions are the waste side slopes and landfill edges. Controls in such areas should be based on horizontal rather than vertical collection systems, reflecting the greater lateral permeability of wastes; such systems would also be more compatible with on-going disposal operations by virtue of minimal disruption to working practices. These control networks could be integrated in due course with permanent gas collection systems for energy recovery.